Epidemiology of Helminthic Infections and Phylogenetic Tree of Strongyloides stercoralis in Rubber Tree Plantation in Lower Northern Part of Thailand - Phuangphet Waree Molee; Apichat Vitta; Somchai Saengamnatdej (Iranian Journal of Parasitology)
Background: Helminthic infections cause helminthiasis, including infections by Strongyloides stercoralis, a kind of helminths that cause reinfection and lead to severe infections, can be transmitted through the soil. We aimed to identify S. stercoralis and other helminthic infections in rubber tree plantations in Thailand's lower northern regions. The specific goals include assessing prevalence using Formalin Ethyl–acetate Concentration Technique (FECT) and Agar Plate Culture (APC) and constructing S. stercoralis phylogenetic tree. Methods: Overall, 646 fecal samples from rubber plantation workers in five provinces in northern Thailand were examined using FECT and APC under microscope. DNA from larvae confirmed as Strongyloides spp. by Polymerase Chain Reaction (PCR) was sequenced for phylogenetic analysis. The DNA sequences were also submitted to the GenBank database. Results: Prevalence of helminthic infections was 8.82%, with soil transmitted helminths (STH) prevalence at 6.81%; S. stercoralis accounted for 5.41%, with Ascaris lumbricoides at 0.62%, hookworm 0.46%, and T. trichiura 0.31%. PCR analysis successfully amplified the 18S rRNA gene in 26 out of 34 genomic DNAs, indicating a detection rate of 70.59%. Sequencing of these PCR products identified S. stercoralis strains closely related to those reported in the Republic of Lao, Myanmar, and Japan, suggesting genetic diversity within the species. Conclusion: STH prevalence, predominantly S. stercoralis, highlights public health concerns in rubber plantation areas, necessitating enhanced monitoring and intervention strategies. Phylogenetic analysis of S. stercoralis, revealing a close genetic relationship among strains from various Southeast Asian countries, which underscores potential patterns of transmission and evolutionary relationships in the regions.